2017
DOI: 10.19044/esj.2017.v13n18p294
|View full text |Cite
|
Sign up to set email alerts
|

Difficultés Relatives A L’enseignement-Apprentissage De La Géologie En Classes Secondaires Qualifiantes Cas De La Délégation d’Inzegane Ait Melloul

Abstract: The present study attempts to identify the difficulties of teaching and learning geology in Moroccan secondary qualifying classes. Teachers of the Life Sciences and Earth Sciences and their pupils at the Inzegane Ait Melloul delegation were administered questionnaires. Based on the analysis of the themes taught and the typologies of obstacles evoked, a bibliographic synthesis allowed us to list the notions which are likely to pose the difficulties presumed in geology. Thus, 23 open and closed questions were di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
2
0
1
Order By: Relevance
“…These future teachers therefore do not master all fossilization processes. Eddif (2017) and Rassou et al (2017) have also identified the problem of a lack or inadequacy of knowledge of geological phenomena, by examining the initial representations of geological concepts held by future science and technology teachers. These authors show that this is a training gap that can hinder the understanding and subsequent transposition of geological concepts into the classroom.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These future teachers therefore do not master all fossilization processes. Eddif (2017) and Rassou et al (2017) have also identified the problem of a lack or inadequacy of knowledge of geological phenomena, by examining the initial representations of geological concepts held by future science and technology teachers. These authors show that this is a training gap that can hinder the understanding and subsequent transposition of geological concepts into the classroom.…”
Section: Discussionmentioning
confidence: 99%
“…who looked at the analysis of teachers' conceptions of biological diversity.Although the participants had already had initial training in phylogeny, they presented errors and inaccuracies, both in definitions and in conceptual applications. They argue that more investment in training is needed Rassou et al (2017). highlighted a gap in the training of future LES teachers.…”
mentioning
confidence: 99%
“…Dans le système éducatif marocain, plusieurs facteurs influencent l'acquisition du savoir enseigné. Selon une recherche récente, les élèves sont peu impliqués dans les cours (Rassou et al, 2017). Aussi, les approches pédagogiques utilisées dans les classes sont traditionnelles (Chaali & Chekour, 2018) et les travaux de laboratoire qui favorise la démarche expérimentale sont utilisés occasionnellement (Lamarti et al, 2009).…”
Section: IIunclassified